2008
DOI: 10.1002/app.28569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(methyl methacrylate) polymerized by microwave energy or conventional water bath

Abstract: In this work, the influence of three different suspension agents (agar, sodium alginate, and gelatin) in the synthesis of poly(methyl methacrylate) (PMMA) particles is reported. Sodium alginate was the best suspension agent, obtaining characteristics closer to commercial denture base resins. Synthesized particles and two commercial acrylic resins (Acron MC and Lucitone 199) were characterized by light microscopy, scanning electron microscopy, characteristic X-ray energy dispersive spectroscopy, thermogravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
(23 reference statements)
1
22
0
Order By: Relevance
“…When the PMMA-silver nanoparticle mixture reached the plastic phase, it was packed into metallic molds to be polymerized by microwave irradiation at 500 W for 3 minutes. 24 PMMA and PMMA-silver nanoparticle discs were prepared. The commercial acrylic resin, Nature Cryl TM MC (GC America Inc, Alsip, IL), was thermopolymerized following the manufacturer's instructions and used as a control.…”
Section: Pmma-silver Nanoparticle Resin Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the PMMA-silver nanoparticle mixture reached the plastic phase, it was packed into metallic molds to be polymerized by microwave irradiation at 500 W for 3 minutes. 24 PMMA and PMMA-silver nanoparticle discs were prepared. The commercial acrylic resin, Nature Cryl TM MC (GC America Inc, Alsip, IL), was thermopolymerized following the manufacturer's instructions and used as a control.…”
Section: Pmma-silver Nanoparticle Resin Samplesmentioning
confidence: 99%
“…Given that most dental materials release small amounts of various substances into their physiological environment (eg, the pulp and oral cavity), it is important to ensure that the potential cytotoxicity of dental materials is minimal, eg, ISO 10993-3 39 and ISO 10993-5, 24 for cytotoxicity and genotoxicity in biomaterials, respectively. The hazardous and toxic effects of silver nanoparticles have not been studied extensively.…”
Section: Microbial Adhesion and Cellular Compatibilitymentioning
confidence: 99%
“…Polymerization takes place inside the monomer droplets, which are progressively converted into viscous and sticky granules, and finally become rigid polymer particles with characteristic sizes ranging from 50 to 500 µm . If the process is well controlled, the final obtained polymer powder presents the form of spherical beads that are easy to manipulate and separate through filtration …”
Section: Introductionmentioning
confidence: 99%
“…Acosta-Torres and coworkers described the polymerization of MMA by conventional and microwave-assisted heating and compared the particles obtained to commercial PMMA resins for denture base applications. [43] They found that both types of PMMA resins were similar to the commercial samples in terms of granular beads, particle size, transverse deflection, and elastic modulus. Palacios and coworkers studied the effect of microwave activation, applied by a 50 W Portland DMR-41 microwave reactor with thermocouple temperature measurement on the dispersion polymerization rate of MMA and the molecular weights of the corresponding PMMA.…”
Section: Emulsion/dispersion Polymerizationsmentioning
confidence: 96%